Linking determinants of the parents’ perception on the effectiveness of community based rehabilitation programmes (CBR). A case of 4 selected CBR services centre in Seremban / Ahmad Syukri Ahmad … [et al.] - Ahmad, Ahmad Syukri; Muhammad, Mohd Ikhfan; A Samad, Suhaimi; Rabun, Mohd Nazir; Haris, Siti Melinda (Universiti Teknologi MARA, 2021)
The New Economic Model introduced in 2010 has emphasised the inclusiveness of every society in socioeconomic development to become a developed nation in 2020. Among targeted groups emphasised by the government is the person with disability, which contribute to 1.2 % of Malaysia’s population. One of the continuous efforts by the government to accelerate this objective is by strengthening the Community Based Rehabilitation Program (CBR), which was implemented in 1984 to assist person with disabilities (PWDs) with basic living skills. This program was pioneered by the World Health Organisation (WHO) following the Declaration of Alma-Ata in 1978 to enhance the quality of life for people with disabilities and their families, meet their basic needs, and ensure their inclusion and participation. Thus, this study aims to examine the level of effectiveness of CBR and to determine the relationship between participation level, module and syllabus, social workers and social support system and the effectiveness of CBR program on 4 selected centres in Seremban, Negeri Sembilan. The sample consists of 121 respondents who are the parents of the trainees. The sampling method used is purposive sampling as the parents would be the suitable ones to deliver the information required for the study. Based on the input obtained from 121 parents, the results found that trainees are indeed showing moderate level of effectiveness of CBR program. The finding reveals a significant correlation of participation level, module and syllabus, social workers and social support system with the level of effectiveness of CBR program. The study found that the participation of trainees had the highest correlation with the level of effectiveness of the CBR in Seremban. Therefore, the trainee’s participation level should be the main focus as it is the most essential part in the successful implementation of the program.